War trauma and strategies for coping with stress among Ukrainian refugees staying in Poland - Piotr Długosz (Elsevier, 2023)
Objectives: The Russian military aggression against Ukraine resulted in a humanitarian crisis. There was a mass exodus of war refugees. More than 17 million people have left Ukraine since the war broke out. The refugees who came to Poland and other countries have experienced war trauma. The study aims to assess mental health of Ukrainian war refugees in Poland. Population and methods: At the time of the study, that is, in April and May 2022, between 1,5 million and 2 million Ukrainian refugees were staying in Poland. They were mainly young women with their children. The CAWI (Computer-Assisted Web Interview) technique was used in the study. The research sample was selected using purposive sampling. The invitation to take part in the survey was posted on social media for Ukrainians in Poland, and also sent to the participants of a Polish as a Foreign Language course. The study utilizes the RHS-15 and a nominal scale measuring the strategies for coping with stress. Results: The research sample consists of 737 respondents. The results of the screening tests indicate that depression, anxiety disorders and PTSD may be observed among 73% of respondents, whereas 66% of the respondents display psychological distress. The analyses have shown that higher levels of mental health disorders were observed among women and refugees who do not speak Polish. Younger respondents experienced a higher psychological distress. The results of the study also indicate that the refugees more often implemented problem-focused strategies. The analysis has shown that the respondents who followed active strategies scored the lowest on RHS-15. The emotion-focused strategies, such as praying, diverting attention by becoming involved in different activities or taking sedatives were not effective. The highest levels of disorders were present among the refugees who indicated resignation. Conclusions: The collected observations indicate that the main problem which might hinder their adaptation could be mental health issues, which in turn impact the general deterioration of health and the quality of life.